Formulation and SPF Evaluation of a Lip Oil Serum Combining Ethanol Extract of Butterfly Pea Flower and Lavender Oil - Annisa Fatmawati; Sundari Desi Nuryanti; Emelda; Ade Puspitasari; Latifa Amalia; Nurus Shobah Salsabila (Media Farmasi Indonesia, 2025)
Exposure to ultraviolet (UV) radiation due to ozone layer depletion increases the risk of skin damage, particularly on the lips, which are more vulnerable due to their lack of melanin and sebaceous glands. This study aimed to formulate and evaluate the Sun Protection Factor (SPF) of a lip oil serum containing ethanol extract of butterfly pea flower (Clitoria ternatea L.) and lavender oil (Lavandula angustifolia). The formulation was prepared in a single base with four variants: a control (F0) and three active concentrations (F1, F2, F3). Physical evaluations included organoleptic tests, homogeneity, pH, spreadability, adhesion, and viscosity. The SPF values were assessed in vitro using UV-Vis spectrophotometry. All formulations demonstrated acceptable physical stability with pH values between 6.7–7.33, spreadability ranging from 6.85–7.34 cm, adhesion from 3.51–5.07 seconds, and viscosity from 777.6–839 cPS. The SPF increased proportionally with lavender oil concentration (F1 = 3.70, F2 = 4.09, F3 = 4.25), showing a strong positive correlation (r = 0.969). These findings suggest that the combined use of butterfly pea extract and lavender oil may offer mild UV protection and desirable physical properties, making it a promising candidate for natural, herbal-based lip care products.